An Inscription from the Amphitheatre of Italica with the Mention TAVRVS IVPPIT[ER] - Caballos Rufino, Antonio (Gerión. Revista de Historia Antigua, 2021)
I present several proposals about a new inscription found in one of the western galleries of the amphitheatre of Italica (Santiponce, Seville). It mentions Tavrvs Ivppit[er] and dates back to the end of third century or the fourth century AD.